2018
DOI: 10.1111/anu.12665
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility coefficients of processed agro-food by-products in European seabass (Dicentrarchus labrax) juveniles

Abstract: Apparent digestibility coefficients (ADCs) of processed agro‐food by‐products were assessed in European seabass (Dicentrarchus labrax). Each experimental diet was obtained by replacing 300 g/kg of a commercial‐based diet used as reference (REF) with a test ingredient: wheat germ (GERM), okara meal (OKA), poultry by‐product meal (POULT), steam hydrolysed (FeHY) and enzyme‐treated feather meal (FeENZ), beta‐lactoglobulin (β‐Lg) and peptide fractions >3,000 Da obtained from brewer's yeast (YeastP) and fish by‐pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Therefore, the PLANT diet formulation included several plant glutens and concentrates, and also plant by‐products, such as wheat germ, guar meal, carob germ and wheat DDGS. Studies on the inclusion of these plant by‐products in aquafeeds are relatively recent and scarce for carnivorous fish species, but in general report good perspectives for their use (e.g., Campos, Matos, Aragão, Pintado, & Valente, ; Couto et al, ; Diógenes, Castro, Miranda, Oliva‐Teles, & Peres, ; Pach & Nagel, ). To the best of our knowledge, there are no available studies reporting the mixture of so many plant by‐products in fish diets.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PLANT diet formulation included several plant glutens and concentrates, and also plant by‐products, such as wheat germ, guar meal, carob germ and wheat DDGS. Studies on the inclusion of these plant by‐products in aquafeeds are relatively recent and scarce for carnivorous fish species, but in general report good perspectives for their use (e.g., Campos, Matos, Aragão, Pintado, & Valente, ; Couto et al, ; Diógenes, Castro, Miranda, Oliva‐Teles, & Peres, ; Pach & Nagel, ). To the best of our knowledge, there are no available studies reporting the mixture of so many plant by‐products in fish diets.…”
Section: Discussionmentioning
confidence: 99%
“…Brestenský, Nitrayová, Patráš, and Heger () tested the digestibility of a WG‐based diet in piglets and found that the protein fraction was highly digestible (85%) and that individual amino acid ADCs were similar to those observed in the reference protein source for pig diets (soybean meal). The ADC of WG was tested in few fish species and was shown to be high in bluntnose black bream (90% protein ADC; Zhou, Ren, Zeng, & Yao, ) as well as in European seabass (97% protein ADC; Campos et al, ). Also, other wheat fractions have been previously tested successfully in fish feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already assessed the incorporation of WG in feeds for farmed pigs with promising results (Brestenský, Nitrayová, Patráš, & Heger, 2013a,2013bRosenfelder, Eklund, & Mosenthin, 2013). A recent study showed that WG is well digested by European seabass (protein ADC of 97% DM; Campos, Matos, Aragão, Pintado, & Valente, 2018) and suggested this ingredient as a promising protein source for this species. Nonetheless, information concerning the incorporation of WG in fish feeds is still very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Fishmeal produced from whole fish besides the high protein content is also a great source of fatty acids and minerals and has been widely used in diets due to its high palatability and balanced amino acid profile (Gatlin et al, 2007). However, the intensification of feed production has increased demand for this ingredient, resulting in less availability and elevated fish feed costs (Klinger and Naylor, 2012;Campos et al, 2018), which currently account for 70% of total production costs. Thus, combining protein and energy ingredients in a competitive and environmentally friendly manner is a major challenge for feed formulators (Mungkung et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The determination of apparent digestibility coefficients (ADC) provides the amount of energy and nutrients contained in the fraction of food ingested that is not excreted in the feces (Choubert et al, 1979;De Silva and Anderson, 1998;NRC, 2011) but is used by the animal metabolism (Che et al, 2017). Digestibility tests make it possible to evaluate the potential of ingredients for use in the diet of aquaculture species (Gaylord and Gatlin, 1996;Che et al, 2017;Campos et al, 2018) and are essential to enable formulation of nutritionally balanced diets that maximize fish yields (Oliveira-Filho and Fracalossi, 2006;Glencross et al, 2016), but also to limit fish waste products and improve homeostasis, enhancing the resistance to disease and stress (Pezzato et al, 2009). The nutritional value of feedstuffs varies from species to species and fish development stage (NRC, 2011) due to physiological and morphological differences in the digestive tract and can also be affected by the processing of the ingredients, which can be hydrolyzed and extruded under high heat and pressure, improving digestibility (Fontoura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%